Gamma rays and neutrons attenuation performance of a developed lead borate glass for radiotherapy room - Zeed, Mona Abo; El Shazly, Raed M; Elesh, Eman; El-Mallah, Hanaa M; Saeed, Aly (Radiation protection dosimetry, 2024)
The development of radiation therapy necessitated a continuous R&D for radiotherapy rooms' glass windows to reach the highest levels of protection for the staff of the radiotherapy facility. Therefore, in this article, a novel type of lead borate glass depending on parallel augmenting of lead and boron was produced to be used as gamma-rays and fast and thermal neutrons barriers in radiotherapy rooms. Neutrons and gamma rays’ attenuation parameters, fast neutrons removal cross section ${\varSigma}_R$, thermal neutron total cross section ${σ}_T$, mass attenuation coefficient $σ$, linear attenuation coefficient μ, half-value layer, mean free path, effective atomic number Zeff, effective electron density Neff, and buildup factor for energy absorption (energy absorption buildup factor) and exposure (exposure buildup factor) were studied extensively. Three tools, Phy-X/PSD, EpiXS and XCOM computer programs and the standard mixture rules were utilized to estimate the attenuation parameters. The improvement caused by the augmentation of lead and boron in both gamma rays and neutrons attenuation was evident from the obtained results. The glass containing the highest lead and boron concentration PbB5, 40Pb-50B, which is the most efficient attenuator for gamma rays and both thermal and fast neutrons was recommended to be a distinguished choice as a shield in a radiotherapy room.